Financial sector assessment : a handbook - Weltbank; Internationaler Währungsfonds (World Bank and International Monetary Fund, 2005)
The Handbook presents an overall analytical framework for assessing financial system stability and developmental needs, providing broad guidance on approaches, methodologies, and techniques of assessing financial systems. Although the Handbook draws substantially on World Bank and IMF experience with the Financial Sector Assessment Program (FSAP) and from the broader policy and operational work in both institutions, it is designed for generic use in financial sector assessments, whether conducted by country authorities themselves, or by World Bank and IMF teams